Endemism within endemism: a new species of Austroleptis Hardy, 1920 (Diptera: Austroleptidae) from the Brazilian Atlantic Forest highlands - Fachin, Diego Aguilar; Santos, Charles Morphy D.; de Souza Amorim, Dalton (Zootaxa, 2020)
A third species of the southern temperate tabanomorph genus Austroleptis Hardy, 1920 (Diptera: Austroleptidae)—A. camposgerais sp. nov.—from the Brazilian Atlantic Forest is described and illustrated. A key for the species of the genus in Brazil is provided. Shared derived features indicate a sister group relationship between the new species and A. longirostris Fachin et al., 2018. Whatever the relationships among the species of this clade, however, there is a process of endemism within endemism in the Atlantic Forest: species at higher altitudes undergo vicariance process that do not affect lowland species distributed around the mountain chains. The low number of specimens known from highland species and the very restricted geographic distribution of each species strongly indicate the urgency to protect the natural environments at higher altitudes in Brazil.